Challenges and Opportunities of Sustainable Accounting in the Banking Sector Facing the Latest Global Regulations - Dewi, Yuli (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Sustainable accounting in the banking sector has become a major issue in the global financial industry. With the emergence of recent regulations, such as the International Financial Reporting Standards (IFRS) 9, the Sustainable Finance Disclosure Regulation (SFDR), as well as policies from the Financial Services Authority (OJK) and Bank Indonesia (BI), banks are required to adopt more transparent and socially and environmentally responsible accounting practices. The study aims to analyze the key challenges faced by the banking sector in implementing sustainable accounting, evaluate the readiness of the banking industry to face the latest global regulations, and identify opportunities that banks can take advantage of to align their accounting practices with international sustainability standards. The method used in this study is a literature study with a qualitative approach. Data sources come from scientific journals, regulatory reports, and relevant academic publications in the last five years. The analysis was carried out through the content analysis method to identify patterns, trends, and the relationship between global regulations and the implementation of sustainable accounting in the banking sector. The results show that the main challenges in the implementation of sustainable accounting include regulatory uncertainty, limitations of uniform reporting standards, and lack of an accounting system that is integrated with sustainability principles. However, there is a great opportunity for banks to increase their competitiveness by adopting sustainability standards such as the Global Reporting Initiative (GRI) and the Net-Zero Banking Alliance, as well as leveraging digital technology to improve the transparency of sustainability reporting. Therefore, a more adaptive strategy is needed for the banking sector to ensure compliance with global regulations without sacrificing long-term profitability.